2021
DOI: 10.1021/acs.langmuir.1c01376
|View full text |Cite
|
Sign up to set email alerts
|

Coassembly Behavior and Rheological Properties of a β-Hairpin Peptide with Dicarboxylates

Abstract: To understand the molecular interaction mechanism and develop peptide-based hydrogels, a β-hairpin peptide CBHH was used as the model peptide, and its coassembly performance with succinic, malic, and tartaric dicarboxylates has been investigated with circular dichroism spectroscopy (CD) and atomic force microscopy (AFM). The rheological properties and cell culture performance of the coassembled hydrogels have also been assessed. The results showed that the dicarboxylates could induce the folding and self-assem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…In addition, PI is a red-fluorescent membrane-impermeable drug molecule, and thus is frequently used as a marker for live/dead cell detection. 47–50 It was found that Pep1–PO 4 3− nanoblocks carrying PI molecules can be taken up by HeLa cells, and red fluorescence can be detected in the HeLa cells (Fig. 6), indicating that PI can be released from Pep1–PO 4 3− nanoblocks into the cytoplasm and nucleus rather than entering the cells due to toxicity.…”
Section: Resultsmentioning
confidence: 98%
“…In addition, PI is a red-fluorescent membrane-impermeable drug molecule, and thus is frequently used as a marker for live/dead cell detection. 47–50 It was found that Pep1–PO 4 3− nanoblocks carrying PI molecules can be taken up by HeLa cells, and red fluorescence can be detected in the HeLa cells (Fig. 6), indicating that PI can be released from Pep1–PO 4 3− nanoblocks into the cytoplasm and nucleus rather than entering the cells due to toxicity.…”
Section: Resultsmentioning
confidence: 98%
“…Next, calcein-AM is cleaved by intracellular esterases to yield highly fluorescent and polar calcein (208)(209)(210). When cells are incubated with calcein and co 2+ , both enter the cytoplasm; however, calcein is further captured by mitochondria (211,212). calcein that accumulates in the mitochondria exhibits fluorescent staining, whereas calcein remaining in the cytoplasm or released from the mitochondria into the cytoplasm is rapidly quenched by co 2+ (213)(214)(215)(216)(217)(218)(219).…”
Section: Detection Of Mitochondrial Permeability Transition Poresmentioning
confidence: 99%